Efficacy of Sacubitril/Valsartan Sodium Combined with Simvastatin in Treating Chronic Heart Failure with Arrhythmia and Its Effects on IL-6, IL-8, and TNF-α: Sacubitril/Valsartan and Simvastatin in Heart Failure with Arrhythmia - Li, Jingjing; Wang, Zhihua (Journal of Medical Biochemistry, 2025)
Background: To explore, in conjunction with clinical practice, the efficacy of different pharmacological treatment regimens for patients with chronic heart failure complicated by arrhythmia, and their effects on inflammatory factor levels. Methods: A total of 96 patients with chronic heart failure and arrhythmia treated at our hospital from June 2022 to January 2025 were selected and randomly assigned by envelope method into a combination therapy group and a simvastatin group. The simvastatin group received simvastatin monotherapy, while the combination group was treated with sacubitril/valsartan sodium plus simvastatin. Clinical efficacy was compared between the two groups. Cardiac function, inflammatory factors, arrhythmia episodes, blood lipid levels, and oxidative stress markers were assessed before and after treatment. Adverse reactions in both groups were also observed. Results: The overall effective rate in the combination therapy group (93.75%) was significantly higher than that in the simvastatin group (72.92%) (χ2=7.500, P=0.006). After treatment, the combination group exhibited higher LVEF and lower LVESD and LVEDD levels compared to the simvastatin group (P